1993
DOI: 10.1152/ajpregu.1993.264.5.r877
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drinking on thirst and vasopressin in dehydrated elderly men

Abstract: Inhibition of dehydration-induced arginine vasopressin (AVP) secretion and thirst depends on removal of osmotic and hemodynamic stimuli as well as on preabsorptive oropharyngeal factors that reduce thirst and AVP secretion on drinking before correction of the water deficits. Plasma atrial natriuretic peptide (ANP) levels may also change with drinking. Therefore, the thirst and plasma responses to oral water loads (10 ml/kg) in 10 healthy old (64-76 yr) and young (20-32 yr) 24-h water-deprived men were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 0 publications
4
39
0
5
Order By: Relevance
“…However, the relation between thirst and the rate of fluid intake was maintained in the elderly. These are identical to the results reported by Phillips et al 75) reported that thirst sensation after 24-h water deprivation was attenuated in the elderly. Moreover, there have been several studies suggesting that sodium retention mechanisms are reduced in the elderly; higher [Na + ] sweat due to impairment of the salt reabsorptive ability of sweat gland ducts 69) and the decrease in renal concentrating ability in aging rats due to the impaired responsiveness of the kidney to AVP 76) .…”
Section: Impaired Thermoregulatory and Body Fluid Regulationssupporting
confidence: 92%
“…However, the relation between thirst and the rate of fluid intake was maintained in the elderly. These are identical to the results reported by Phillips et al 75) reported that thirst sensation after 24-h water deprivation was attenuated in the elderly. Moreover, there have been several studies suggesting that sodium retention mechanisms are reduced in the elderly; higher [Na + ] sweat due to impairment of the salt reabsorptive ability of sweat gland ducts 69) and the decrease in renal concentrating ability in aging rats due to the impaired responsiveness of the kidney to AVP 76) .…”
Section: Impaired Thermoregulatory and Body Fluid Regulationssupporting
confidence: 92%
“…To our knowledge, increased tubular reabsorption in the elderly has not been reported. The association of higher plasma urea levels and lower FE urea values in the elderly could reflect a preservation of the tubular effect of vasopressin on urea reabsorption, which possibly differs from the widely known age-related decrease in water reabsorption in the elderly (19 -21), despite an enhanced osmoreceptor sensitivity to vasopressin release (7,22) and higher vasopressin levels (7,(23)(24)(25). In rats, age-associated defects in urine concentration are accompanied by a downregulation of renal vasopressin V 2 receptors and aquaporin-2 expression (26).…”
Section: Discussionmentioning
confidence: 93%
“…Significant changes failed to materialize in the older group for successive comparisons of AVP levels, whereas the young subjects had a much lower baseline level, demonstrated a marked increase during the infusion, and a precipitate decline subsequent to drinking. The age-related attenuation of AVP responses to hypertonic infusion and drinking has precedent in other experimental manipulations of thirst (29). There is evidence from human and animal experimentation to suggest that afferent input from the oropharangeal region is particularly important for the inhibition of AVP release subsequent to drinking (30,31).…”
Section: Discussionmentioning
confidence: 99%